Can Neutrophil-Lymphocyte Ratio and Lymph Node Density Be Used as Prognostic Factors in Patients Undergoing Radical Cystectomy? - Abdullah Demirtaş; Volkan Sabur; Emre Can Akınsal; Deniz Demirci; Oguz Ekmekcioglu; Ibrahim Gulmez; Atila Tatlisen (The Scientific World Journal)
Objective. To assessment the role of preoperative neutrophil-lymphocyte ratio and postoperative lymph node density in predicting prognosis in patients undergoing radical cystectomy for bladder cancer. Material and Methods. Preoperatively, neutrophil and lymphocyte counts as well as neutrophil-lymphocyte ratios were recorded in 201 patients who underwent radical cystectomy for bladder cancer. Patients with an infection were excluded. Based on the pathology reports, the number of positive lymph nodes was divided by the total number of lymph nodes to calculate lymph node density. Results. The mean follow-up duration was months in patients without lymph node involvement and months in those with lymph node involvement (). Median lymph node density was 17% (4–80) in patients with lymph node involvement. There was no difference according to lymph node density lower than 17% and greater than 17% . There was no significant difference between patients with an NLR below or above 2.5 in terms of overall survival (). Pathological T stage was associated with survival (). Conclusion. In patients undergoing RC for bladder cancer, lymph node density and preoperative NLR were not found to be independent predictors of prognosis.